Isolation and Identify the Antibiotic from the Local Isolates of the Streptomyces antibiotics and Test their Antifungal Activity against Plant Pathogens - Safaa Ismail Rashid Al-Obaidi (Journal of Global Pharma Technology, 2020)
A bacterial isolates of (80) from (17) soil samples has been collected from the rhizosphere of different plants of many regions Mosul city; the isolates were initially identified as a Streptomyces genus according to the chalky appearance and the odor of the moist earth. Antagonistic activity against fungi isolated from the soil rhizosphere of plantshas been tested. Only (49) isolates (i.e. 57.64%) proved their antagonized ability against one or more of the tested fungi. The best isolation that gave antifungal efficacy against all fungi, and was the largest diameter of the inhibition area against A. flavus (48 mm) followed by M. Phaseolina (27 mm), the least inhibition zonewas (12 mm) of Sclerotiumcepivorum (12 mm). The isolation elected to the level of the species was identified by the morphological, physiological and hematological tests and was found to belong to the species of Streptomyces lydicus. The identification of the antibiotic extracted by ethyl acetate was done using three solutions that are butanol: pyridine: water (6:3:4), methanol: dichloromethyne: water (1:1:1) and butanol: acetic acid: water (6:4:3). A single spot appeared on a thin-layer chromatography plate (TLC) indicating the production of one type of antibiotic. It was noticed that Rf for the spot in the 3 solvents was 0.82, 0.47, and 0.80 respectively. The solvent with Rf 0.86 was the best hence it gave the highest inhibition for the growth of at least 2 fungi. Ultra violet absorption for the antibiotic was (286) and appeared that this compound was a Macrolides. Also Infra red (IR) was measured suggesting that the expected structure of the antibiotic is Oleandomyein.Key words: Streptomyces antibiotics, Bacteria, Antifungal, TCL plate.